Effect of Different Measurement Tasks on the Frequency of Microsaccades - Ohara, Toumi; Kinoshita, Fumiya (Journal of advanced computational intelligence and intelligent informatics, 2024)
In recent years, several attempts have been made to quantitatively evaluate covert attention using microsaccades. However, several unclear aspects exist regarding the measurement method of microsaccades, and a unified analysis method does not exist. Therefore, the current status is such that the interpretation of the results is divided among the research groups. To address this problem, empirical studies on microsaccades must be accumulated and measured and evaluated using a unified method. Therefore, in this study, to accumulate empirical studies on microsaccades, an experiment was conducted to investigate the effect of the presence or absence of gazing at a fixation point on the interval of occurrence of microsaccades in a measurement task. The participants were 15 healthy young people, and we compared the following two types of measurement tasks. Task-I: The participants freely visually searched a white wall 1 m away for 120 s. Task-II: The participants gazed at a fixation point located 1 m ahead at eye level for 120 s. For the microsaccade detection algorithm, we adopted a method imitating the EK method proposed by Engbert and Kliegl in 2003, divided 120 s of time-series data and analyzed it every 2 s, and subsequently evaluated the time-series data for the entire 120 s by concatenating them. Consequently, the interval of occurrence of microsaccades during Task-II decreased by more than 1 Hz compared with that of Task-I ( p <0.05). The study confirmed that the presence or absence of gazing at the fixation point during microsaccade measurement affected the interval of occurrence of microsaccades.